The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1055/s-0039-1681054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electronic versus Paper-Based Recording before EHR Implementation on Health Care Professionals' Perceptions of EHR Use, Data Quality, and Data Reuse

Abstract: Background The implementation of an electronic health record (EHR) with structured and standardized recording of patient data can improve data quality and reusability. Whether and how users perceive these advantages may depend on the preimplementation situation. Objective To determine whether the influence of implementing a structured and standardized EHR on perceived EHR use, data quality, and data reuse differed for users working with paper-based records versus a legacy EHR before implementation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Several studies demonstrated issues considered as obstacles to the implementation of an EMR system, were mainly associated with a shortage of human resources, hardware and software failure, user resistance, lack of computer literacy, lack of technical expertise, lack of awareness, lack of understanding stakeholders demand, and lack of appropriate ICT infrastructure with facilities and equipment [ 10 , 12 , 15 18 ]. Cost, privacy concerns, lack of uniform standards, resistance, lack of policy support, vendor support and maintenance, and lacking awareness, were mentioned as obstructing EMR system implementation [ 9 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated issues considered as obstacles to the implementation of an EMR system, were mainly associated with a shortage of human resources, hardware and software failure, user resistance, lack of computer literacy, lack of technical expertise, lack of awareness, lack of understanding stakeholders demand, and lack of appropriate ICT infrastructure with facilities and equipment [ 10 , 12 , 15 18 ]. Cost, privacy concerns, lack of uniform standards, resistance, lack of policy support, vendor support and maintenance, and lacking awareness, were mentioned as obstructing EMR system implementation [ 9 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paper-based systems are considered a human resource and time-intensive and are often plagued by inaccurate reporting processes leading to out-of-date and irrelevant data [ 11 ]. Other studies were concluding that patient data in paper records often are vague, ambiguous, incomplete, or hard to extract information from its illegible handwritten pages, has limited opportunities for reuse and sharing of data [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor communication [34,40,47,48,70,78,120] Dysfunctional workflow [29,38,44,45,47,61,73,89,91,[112][113][114][115]141,148] Data and information Data quality and accuracy [40,48,78,91,122,137,145] Decreased accessibility [39,40,43,70,106,126] Care for patients Face-to-face or direct communication [43,45,84,137] Quality of care [20,28,34,38,81,82,94,106,116,126,137,…”
Section: Theme Category Sub-category Referencementioning
confidence: 99%
“…] Hyvien tietojärjestelmien käyttötaitojen ja käyttövarmuuden on osoitettu olevan yhteydessä käytön yleisyyteen ja käytettävien järjestelmien lukumäärään [14,15]. Tietojärjestelmien käyttöön liittyy runsaasti odotuksia, kuten järjestelmän helppokäyttöisyys, hyödyllisyys työtehtäviin tai vaikutukset hoidon laatuun ja jatkuvuuteen, ja nämä toteutuvat hitaasti [16][17][18][19][20]. Vaikutukset käyttöönotosta saadaan esiin usein vuosien viiveellä [16,21].…”
Section: 102020unclassified